Leiomyoma of the Trachea: a case report - Kitada, Masahiro (J Cardiothorac Surg, 2015)
We present a surgical case of a rare primary tracheal tumor. In a 44-year-old asymptomatic man, computed tomography (CT), performed as part of health check-up, revealed a tumor measuring 1.5 cm in diameter in the mediastinal trachea. Biopsy failed to yield a definitive diagnosis, but the tumor tended to grow rapidly; therefore, surgery was performed. Five tracheal rings were resected through median sternotomy, followed by interrupted suture with 3–0 absorbable thread. The postoperative course has been favorable with no evidence of recurrence. The pathological diagnosis was leiomyoma. We report this case with literature review.